2020
DOI: 10.1038/s41467-020-17429-5
|View full text |Cite
|
Sign up to set email alerts
|

The circadian phase of antenatal glucocorticoid treatment affects the risk of behavioral disorders

Abstract: During pregnancy, maternal endocrine signals drive fetal development and program the offspring's physiology. A disruption of maternal glucocorticoid (GC) homeostasis increases the child's risk of developing psychiatric disorders later in life. We here show in mice, that the time of day of antenatal GC exposure predicts the behavioral phenotype of the adult offspring. Offspring of mothers receiving GCs out-of-phase compared to their endogenous circadian GC rhythm show elevated anxiety, impaired stress coping, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 75 publications
1
31
0
2
Order By: Relevance
“…There is already evidence that the circadian system synchronizes maternal metabolic adaptations in the liver to support fetal growth (Papacleovoulou et al, 2017;Wharfe et al, 2016). Meanwhile, the fetal circadian system develops and gains autonomy towards term (Astiz et al, 2020;Landgraf et al, 2015;Wharfe et al, 2011) under the influence of endogenous and exogenous signals crossing the feto-maternal interphase, the placenta (Mendez et al, 2016;Smarr et al, 2017;Varcoe et al, 2011Varcoe et al, , 2013Varcoe et al, , 2018Vilches et al, 2014). Recent evidence has shown clock gene expression in several fetal tissues including the LZ of the placenta by mid gestation in rodents (C ̌ecmanová et al, 2019;Landgraf et al, 2015;Waddell et al, 2012;Crew et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is already evidence that the circadian system synchronizes maternal metabolic adaptations in the liver to support fetal growth (Papacleovoulou et al, 2017;Wharfe et al, 2016). Meanwhile, the fetal circadian system develops and gains autonomy towards term (Astiz et al, 2020;Landgraf et al, 2015;Wharfe et al, 2011) under the influence of endogenous and exogenous signals crossing the feto-maternal interphase, the placenta (Mendez et al, 2016;Smarr et al, 2017;Varcoe et al, 2011Varcoe et al, , 2013Varcoe et al, , 2018Vilches et al, 2014). Recent evidence has shown clock gene expression in several fetal tissues including the LZ of the placenta by mid gestation in rodents (C ̌ecmanová et al, 2019;Landgraf et al, 2015;Waddell et al, 2012;Crew et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the functionality of clocks of fetal origin have been questioned as not all the members of the interlocked TTFL are rhythmically expressed in the circadian range, as they are in adult tissues. Therefore, fetal clocks have been considered to be slave oscillators entrained by maternal rhythmic signals crossing placenta (Astiz et al, 2020;Crew et al, 2018;Honma, 2020;Houdek and Sumová, 2014;Mendez et al, 2012;Reppert and Schwartz, 1984;Serón-Ferré et al, 2012). Some of those signals freely cross the placenta (and convey the external time to the fetus) and some others are metabolized by enzymes expressed in the LZ (Christ et al, 2012;Houdek et al, 2016;Krozowski et al, 1999;Mark et al, 2017;Okatani et al, 1998;Waddell et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, most rodent prenatal stress paradigms entail some degree of circadian disruption because the animals are manipulated during their normal rest phase. We have recently demonstrated that the offspring from mothers exposed to GCs during the rest phase show worse circadian and stress-related behavioral phenotypes than those from mothers exposed to the same GC concentration, but during the active phase (Astiz et al, 2020). Much less is known about other signals that are also rhythmic in the mother and are known to cross the placenta or to impact on fetus development such as leptin.…”
Section: The Maternal Circadian System During Pregnancy and Early Posmentioning
confidence: 99%
“…Recent data from our lab show that the circadian phase of GCs that reach fetal tissues determines their effectiveness in programing the offspring’s circadian behavior. This temporal gating originates from the embryonic clock system and may involve rhythmic expression of the negative GR modulator Reverse erythroblastoma (REV-ERB α/β aka Nr1d1/2 ) ( Astiz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous factors such as brain immaturity and dysregulated immune responses leading to inflammation-mediated morbidity play a crucial role [3]. Environmental factors such as intensive care, stress, maternal separation, nutritional deficits, circadian rhythm disruption, antibiotics and steroids have also been associated with altered brain development and may therefore contribute to the risk profile of VLBW children [2][3][4][5][6][7]. All these factors have an impact on fragile immune-microbiome co-establishment in preterm children, which occurs in timely association with central nervous system (CNS) development.…”
Section: Introductionmentioning
confidence: 99%